Clinico-pathological study of mucormycosis in post-COVID patients at government general hospital, Nizamabad - Manisha Thavanam; Farida Begum; Seshava Puri Smitha Vadana; Nagarjuna Chary Rajarikam; Harish Swamy Dharmagadda (Asian Journal of Medical Sciences, 2023)
Background: Mucormycosis is a rare, opportunistic fungal infection with high morbidity and mortality. Coronavirus disease 2019 (COVID-19) associated mucormycosis has been increasing in frequency since early 2021, particularly among patients with uncontrolled diabetes and systemic corticosteroid treatment. Aims and Objectives: The aim of the study was to study mucormycosis occurrence in COVID-19 patients at Government General Hospital, Nizamabad – A tertiary care center and to correlate mucormycosis with comorbidities and previous treatment modalities among admitted post COVID-19 patients. Materials and Methods: Cross-sectional retrospective study was done for 3 months, from June 2021 to August 2021. Fifty suspected cases of mucormycosis specimens sent to the Department of Pathology, Government General Hospital, Nizamabad for histopathological diagnosis were considered. Clinical history and treatment details were noted. Tissues obtained were fixed in 10% formalin, routine hematoxylin and eosin (H&E) stains were done. Gomori’s methenamine silver stains were done. Results: Mucormycosis was most common in males 37 (74%) and common in the age group of 41–50 years (26%). Diabetes mellitus is the most common comorbidity (60%). The mean duration between diagnosis of COVID-19 and development of symptoms of mucor was 6–40 days. Out of 50 cases, 46 patients received steroid therapy and 39 cases were given oxygen support. Conclusion: Mucormycosis is a rapidly progressive life-threatening opportunistic infection. Post COVID-19 patients with uncontrolled diabetes are more prone to it and an important predisposing factor. Treatment with steroid therapy and oxygen support must be carefully monitored and used in a vigilant manner. Histopathological examination and clinical correlation are essential for early diagnosis and treatment.